How Primary Care Providers Talk to Patients About Alcohol: A Qualitative Study - McCormick, Kinsey A (Blackwell Science Inc, 2006)
BACKGROUND: Alcohol misuse is a common and well-documented source of morbidity and mortality. Brief primary care alcohol counseling has been shown to benefit patients with alcohol misuse. OBJECTIVE: To describe alcohol-related discussions between primary care providers and patients who screened positive for alcohol misuse. DESIGN: An exploratory, qualitative analysis of audiotaped primary care visits containing discussions of alcohol use. PARTICIPANTS: Participants were 29 male outpatients at a Veterans Affairs (VA) General Internal Medicine Clinic who screened positive for alcohol misuse and their 14 primary care providers, all of whom were participating in a larger quality improvement trial. MEASUREMENTS: Audiotaped visits with any alcohol-related discussion were transcribed and coded using grounded theory and conversation analysis, both qualitative research techniques. RESULTS: Three themes were identified: (1) patients disclosed information regarding their alcohol use, but providers often did not explore these disclosures; (2) advice about alcohol use was typically vague and/or tentative in contrast to smoking-related advice, which was more common and usually more clear and firm; and (3) discomfort on the part of the provider was evident during alcohol-related discussions. LIMITATIONS: Generalizability of findings from this single-site VA study is unknown. CONCLUSION: Findings from this single site study suggest that provider discomfort and avoidance are important barriers to evidence-based brief alcohol counseling. Further investigation into current alcohol counseling practices is needed to determine whether these patterns extend to other primary care settings, and to inform future educational efforts.